Determinants of feedback retention in soccer players - Januario, N.; Rosado, A.; Mesquita, I.; Gallego, J.; Aguilar-Parra, J. M. (Journal of Human Kinetics, 2016)
This study analyzed soccer players` retention of coaches` feedback during training sessions. We intended to determine if the retention of information was influenced by the athletes` personal characteristic (age, gender and the sports level), the quantity of information included in coach`s feedback (the number of ideas and redundancy), athletes` perception of the relevance of the feedback information and athletes` motivation as well as the attention level. The study that was conducted over the course of 18 sessions of soccer practice, involved 12 coaches (8 males, 4 females) and 342 athletes (246 males, 96 females), aged between 10 and 18 years old. All coach and athlete interventions were transposed to a written protocol and submitted to content analysis. Descriptive statistics and multiple linear regression were calculated. The results showed that a substantial part of the information was not retained by the athletes; in 65.5% of cases, athletes experienced difficulty in completely reproducing the ideas of the coaches and, on average, the value of feedback retention was 57.0%. Six variables with a statistically significant value were found: gender, the athletes` sports level, redundancy, the number of transmitted ideas, athletes` perception of the relevance of the feedback information and the athletes` motivation level.